Calcium signaling in oocyte quality and functionality and its application - Chen, Chen; Huang, Zefan; Dong, Shijue; Ding, Mengqian; Li, Jinran; Wang, Miaomiao; Zeng, Xuhui; Zhang, Xiaoning; Sun, Xiaoli (Frontiers in Endocrinology, 2024)
Calcium (Ca2+) is a second messenger for many signal pathways, and changes in intracellular Ca2+ concentration ([Ca2+]i) are an important signaling mechanism in the oocyte maturation, activation, fertilization, function regulation of granulosa and cumulus cells and offspring development. Ca2+ oscillations occur during oocyte maturation and fertilization, which are maintained by Ca2+ stores and extracellular Ca2+ ([Ca2+]e). Abnormalities in Ca2+ signaling can affect the release of the first polar body, the first meiotic division, and chromosome and spindle morphology. Well-studied aspects of Ca2+ signaling in the oocyte are oocyte activation and fertilization. Oocyte activation, driven by sperm-specific phospholipase PLCζ, is initiated by concerted intracellular patterns of Ca2+ release, termed Ca2+ oscillations. Ca2+ oscillations persist for a long time during fertilization and are coordinately engaged by a variety of Ca2+ channels, pumps, regulatory proteins and their partners. Calcium signaling also regulates granulosa and cumulus cells’ function, which further affects oocyte maturation and fertilization outcome. Clinically, there are several physical and chemical options for treating fertilization failure through oocyte activation. Additionally, various exogenous compounds or drugs can cause ovarian dysfunction and female infertility by inducing abnormal Ca2+ signaling or Ca2+ dyshomeostasis in oocytes and granulosa cells. Therefore, the reproductive health risks caused by adverse stresses should arouse our attention. This review will systematically summarize the latest research progress on the aforementioned aspects and propose further research directions on calcium signaling in female reproduction.